Magnetic mesoporous FeCo2O4–Fe3O4 microrods as novel peroxymonosulfate activators for effective metronidazole degradation. Issue 12 (14th July 2020) - Ren, Hejun; Li, Chenguang; Han, Zhonghui; Li, Tingting; Jin, Xiong; Zhou, Rui
Abstract: BACKGROUND: Metronidazole (MNZ) is a highly typical representative antibiotic widely occurring in wastewaters. Its release poses potential threats to the environment and human health. Advanced oxidation processes based on heterogeneous catalysis are promising technologies for organic matter removal. In this study, a new type of magnetic mesoporous FeCo2 O4 –Fe3 O4 microrods was prepared and evaluated as catalyst to activate peroxymonosulfate (PMS) for metronidazole (MNZ) degradation. RESULTS: The effects of catalyst dosage, PMS concentration, and pH on MNZ degradation were investigated. A 96.8% removal of MNZ (100 mg L −1 ) was attained in the FeCo2 O4 –Fe3 O4 /PMS under the optimum conditions of 4 mM PMS, 0.4 g L −1 FeCo2 O4 –Fe3 O4 loading, pH 7 and 60 min reaction time. The hydroxyl radicals (OH) and sulfate radicals (SO4 − ) were identified as the primary reactive species attributed to MNZ removal. The plausible mechanism of the catalytic degradation was proposed and assumed to be related to the Co/Fe species that exerted the synergistic effect during reactions. FeCo2 O4 –Fe3 O4 showed excellent reusability and stability, which was testified by the successive degradation experiments. More importantly, FeCo2 O4 –Fe3 O4 exhibited general applicability in eliminating various antibiotics, including ciprofloxacin, 2, 4‐dichlorophenol, ofloxacin, and tetracycline. The efficiencies of which were 78.8%, 77.1%, 81.3%, and 60.7%, respectively, under identical reaction conditions as MNZ. CONCLUSION: This study proved that mesoporous FeCo2 O4 –Fe3 O4 microrods are efficient PMS activators and provided a novel strategy for developing FeCo2 O4 –based catalysts for the removal of organic pollutants from water. © 2020 Society of Chemical Industry